Perlindungan Hukum Bagi Pemilik Hak Atas Tanah Dalam Pelaksanaan Musyawarah Ganti Rugi Pengadaan Tanah - Bha'iq Roza Rakhmatullah; Achmad Irwan Hamzani; Soesi Idayanti; Evy Indriasari; Zamzam Muhammad Fuad (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Prior to the implementation of the awarding of compensation to land rights interns, a compensation deliberation procedure was carried out. In the implementation of compensation deliberations, the chief executor of land acquisition will convey the results of the assessment of the value of compensation carried out by the Land Appraisal Team (Appraisal). In the compensation deliberations, the entitled party who has not been issued only provides a way to submit an objection to the District Court. The formulation of the problem in this study is how to take legal action against land rights owners against compensation value violence and how to realize legal protection for fair land rights owners in the implementation of compensation deliberations. The type of research used in this research is normative juridical. Normative juridical research is library law research that is carried out by examining library materials or secondary data. The results of the study are legal remedies that can be taken by owners of land rights against compensation value violence, namely by submitting objections to the local district court and to fulfill legal protection of the rights of landowners and realize a sense of justice, preferably in the implementation of compensation deliberations, owners of land rights are given the right to enforce coercion in order to reach consensus on the results of the Land Assessment Team's assessment (Appraisal) and other legal remedies are needed for landowners who refuse large compensation. Suggestions in this study are that it is necessary to carry out revisions to laws and regulations regarding land acquisition and it is necessary to increase socialization to the community regarding event activities in the implementation of compensation deliberations, including also providing assistance to people who reject the results in the implementation of compensation deliberations.Keywords: Deliberation; Compensation; Fair AbstrakSebelum pelaksanaan pemberian ganti rugi kepada pemagang hak atas tanah, maka dilakukan prosedur musyawarah ganti rugi. Dalam pelaksanaan musyawarah ganti rugi, ketua pelaksana pengadaan tanah akan menyampaikan hasil penaksiran nilai ganti rugi yang dilaksanakan Tim Penilai Pertanahan (Appraisal). Dalam musyawarah ganti rugi, Pihak yang berhak yang belum sepakat hanya diberikan jalan untuk mengajukan keberatan kepada Pengadilan Negeri. Rumusan permasalahan dalam penelitian ini adalah Bagaimana upaya hukum pemilik hak atas tanah terhadap penolakan nilai ganti rugi dan bagaimana mewujudkan perlindungan hukum bagi pemilik hak atas tanah yang berkeadilan dalam pelaksanaan musyawarah ganti rugi. Jenis penelitian yang dipergunakan dalam penelitian ini adalah yuridis normatif. Penelitian yuridis normatif adalah penelitian hukum kepustakaan yang dilakukan dengan cara meneliti bahan-bahan kepustakaan atau data sekunder. Hasil penelitian adalah upaya hukum yang dapat dilakukan oleh pemilik hak atas tanah terhadap penolakan nilai ganti rugi, yaitu dengan mengajukan keberatan kepada pengadilan negeri setempat dan untuk memenuhi perlindungan hukum terhadap hak-hak pemilik tanah dan mewujudukan rasa keadilan, sebaiknya dalam pelaksanaan musyawarah ganti rugi, pemilik hak atas tanah diberikan hak untuk melaksanakan perundingan guna mencapai mufakat terhadap hasil penilaian Tim Penilai Pertanahan (Appraisal) dan perlu disediakan upaya hukum lainnya bagi pemilik tanah yang menolak besaran ganti rugi. Saran dalam penelitian ini adalah perlu dilaksanakan revisi terhadap peraturan perundang-undangan tentang pengadaan tanah dan perlu meningkatkan sosialisasi terhadap masyarakat mengenai kegiatan acara dalam pelaksanaan musyawarah ganti rugi, termasuk juga pemberian pendampingan terhadap masyarakat yang menolak hasil dalam pelaksanaan musyawarah ganti rugi.Kata Kunci: Musyawarah; Ganti Rugi; Adil